Historical and Theological Study: The Concept of the Seven Heavens and Their Awaited Prophet in the Perspective of the Qur’an and Hadith - Junaedi, Abdul Wahab; Sartika, Ela (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The concept of the seven heavens in the Qur’an and Hadith is an important phenomenon that has attracted the attention of scholars and the general public throughout Islamic history. While the Qur’an mentions the seven heavens as an affirmation of Allah’s greatness, explanations regarding the guardian prophets of the heavens are more extensively found in Hadith through the event of Isra and Mi'raj. This research aims to explore the concept of the seven heavens and their guardian prophets in the context of the Qur’an and Hadith using historical and theological approaches. The research method employed is qualitative study with descriptive analysis. The findings indicate that various interpretations of the seven heavens emerge among scholars, including literal and symbolic interpretations, illustrating the limitations of human knowledge. This study also emphasizes the importance of dialogue between the interpretation of the Qur’an and modern knowledge. The contribution of this research is to enrich the theological and cosmological understanding of Muslims regarding the concept of the seven heavens while demonstrating its relevance in contemporary scientific contexts.